2018
DOI: 10.1002/uog.17447
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hemodynamics early in labor: a possible link with obstetric risk?

Abstract: The study of maternal cardiovascular adaptation at the end of pregnancy could help to identify low-risk patients who may develop complications during labor. In particular, low cardiac output and high total vascular resistance are apparently associated with higher risk of fetal distress or maternal complications. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
5
16
0
Order By: Relevance
“…The screen-positive women would struggle to accommodate the 12% and 34% increases in CO associated with the first and second stages of labor, respectively 2,37 , or the hypovolemic stress after epidural anesthesia 38,39 . It is thus unsurprising that women with low CO and high PVR had more intrapartum fetomaternal complications 40 , as also demonstrated in this study. This is the first study that utilizes a validated combined multimarker screening method to select a high-and low-risk-for-PE cohort for the comparison of maternal hemodynamics.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The screen-positive women would struggle to accommodate the 12% and 34% increases in CO associated with the first and second stages of labor, respectively 2,37 , or the hypovolemic stress after epidural anesthesia 38,39 . It is thus unsurprising that women with low CO and high PVR had more intrapartum fetomaternal complications 40 , as also demonstrated in this study. This is the first study that utilizes a validated combined multimarker screening method to select a high-and low-risk-for-PE cohort for the comparison of maternal hemodynamics.…”
Section: Discussionsupporting
confidence: 76%
“…The screen‐positive women would struggle to accommodate the 12% and 34% increases in CO associated with the first and second stages of labor, respectively, or the hypovolemic stress after epidural anesthesia. It is thus unsurprising that women with low CO and high PVR had more intrapartum fetomaternal complications, as also demonstrated in this study.…”
Section: Discussionsupporting
confidence: 53%
“…Tiralongo et al 25 demonstrated significantly more complications and poorer outcomes in the group with SVR greater than 1200 dynes × s/cm 5 . In terms of SVR, our findings are in agreement with that of previous studies; with the group that underwent operative delivery due to presumed fetal compromise having a significantly higher median SVR than the group that delivered without fetal compromise 17 . It has been suggested that, under normal circumstances, vascular remodeling of the spiral arteries allows for a decrease in SVR, and thus an improved blood flow, which reduces the chances of the fetus suffering from hypoxia 17 .…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have identified SVR as a key predictor of intrapartum complications, including fetal distress. Valensise et al 17 demonstrated a raised SVR to be associated significantly with fetal distress and Vasapollo et al 24 determined an elevated SVR to be the best predictor of intrapartum complications. Tiralongo et al 25 demonstrated significantly more complications and poorer outcomes in the group with SVR greater than 1200 dynes × s/cm 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently a new device has been introduced for the measurement of SV and CO in pregnancy, the UltraSonic Cardiac Output Monitor (USCOM 1A®). This is a non‐invasive hemodynamic monitor that measures cardiovascular values by using a non‐imaging continuous‐wave Doppler transducer placed on the suprasternal notch to determine ascending transaortic blood flow (Figure ).…”
Section: Methods Of Co Measurementmentioning
confidence: 99%